JOURNAL REVIEW : STRATEGI UNTUK MENERAPKAN TALENT MANAGEMENT (MANAJEMEN TALENTA) DALAM PERUSAHAAN - Rachmawati, Meida (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2014)
Abstract People are the most important resource of a Software Company. Software companies especially have always had to compete for the best and brightest. Facing growing competition for the talent they need, they work harder and longer at keeping their best, developing skills internally, and always on the lookout to attract the best and brightest. The purpose of this paper is to provide an in-depth look into where retailers are succeeding on the talent front – and where they are coming up short. The research design used in this study is descriptive and conceptual framework of this research is based on theoretical and design principles. This paper draws on a survey of 112 organizations to investigate how talent management strategies affect organizational performance in software companies. The findings from this study are talent management practices with a strong focus on business strategy and its alignment with overall business goals. These practices have statistically highly significant impact on corporate profits; one that is greater than that of any other focus of talent management practices. This research paper suggested that the management and individuals need to establish metrics and communicate the impact of the organization’s talent management efforts. Keywords: Talent management, corporate strategy, succession planning, human capital